Investigation and techno-economic basis of introduction expediency of complex gabion construction production - Radkevych, A. V.; Horbatiuk, Yu. M.; Yevin, Y. M.; Yakovliev, S. O. (Science and Transport Progress, 2010)
The modern approaches to the solution of problem of expedience of introducing the complex production of mesh structures on the base of structural subdivisions of the Government Special Service of Transport are examined.